2020
DOI: 10.5093/pi2020a7
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation after Divorce: An RCT Study of the Effects of a Digital Intervention Platform on Self-Perceived Stress

Abstract: In most industrialized societies, including Denmark where the current study was conducted, the divorce rate exceeds 40% (Centers for Disease Control and Prevention, 2016; European Commission, 2015; Statistics Denmark, 2017). Divorce has consistently been found to be among the most stressful life events and is often perceived as a prolonged stressful situation by divorcees (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 50 publications
(69 reference statements)
0
42
1
1
Order By: Relevance
“…The decline may be due to an adverse time effect of mental health on physical health whereby reduced mental health increasingly adversely affects physical health over time. In this regard, although we found that mental health increased over time in our study in the control group also, mental health more generally has still consistently been found to be poorer among divorcees than comparable norm groups both immediately following divorce and at 1-year assessments from baseline (see also Cipric et al, 2020;Hald et al, 2020). While we find little reason to think that this may be different in the current study, we encourage future studies in the area to allow for designs investigating this hypothesis.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The decline may be due to an adverse time effect of mental health on physical health whereby reduced mental health increasingly adversely affects physical health over time. In this regard, although we found that mental health increased over time in our study in the control group also, mental health more generally has still consistently been found to be poorer among divorcees than comparable norm groups both immediately following divorce and at 1-year assessments from baseline (see also Cipric et al, 2020;Hald et al, 2020). While we find little reason to think that this may be different in the current study, we encourage future studies in the area to allow for designs investigating this hypothesis.…”
Section: Discussioncontrasting
confidence: 55%
“…Given that other papers have reported CAD program effects on outcomes such as stress, anxiety, depression, somatisation, and hostility (Cipric et al, 2020Øverup et al, 2020), the current findings further speak to the breadth of the effects of the CAD program and highlight its potential public health significance. Importantly, the results for mental health in this study are on par with those previously reported for more specific mental health outcomes such as depression or anxiety (Hald et al, 2020).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Second, most countries in the world require separation periods before juridical divorce is granted. This means that divorce studies able to employ "real-time" research are scarce and there has been a call for such studies (e.g., Thuen, 2001;Cipric et al, 2020). The concept of "real-time" research usually refers to the collection of data among divorcees with little or no separation periods before formal juridical divorce (Hald et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%